Genetic Diversity of HPV-16 E6, E7, and L1 Genes in Women With Cervical Lesions in Liaoning Province, China. Issue 3 (1st April 2011) - Sun, Zhengrong; Ren, Gaowei; Cui, Xin; Zhou, Weiqiang; Liu, Chao; Ruan, Qiang
Abstract : Introduction: High-risk human papillomaviruses (HPVs) play a cardinal role in the etiology of cervical cancer. The most prevalent type, HPV-16, shows intratypic sequence variants that are known to differ in oncogenic potential and geographic distribution. Intratype variations in oncogenic E6/E7 and capsid L1 proteins of HPV-16 are associated with risk of viral persistence and progression. Methods: This study was designed to analyze sequence variations in E6, E7, and L1 genes of HPV-16 in patients with cervical lesion to identify the most prevalent and novel HPV-16 variants in northern China. Results: Our results showed that HPV-16 variants with respect to E6 and E7 were high prevalence of the Asian lineage: 48.3% and 51.4%, respectively. Sequences of the E6 gene revealed 4 amino acid changes of variants D25E and L83V, with 48.3% (69/143) and 11.2% (16/143), respectively, and variants H78Y and E113D in this study. The results also showed the prevalence of 4 hot spots of E7 nucleotide variations leading to N29H, N29S, and 2 silent variations, nucleotide G666A and nucleotide T846C, with 4.2% (6/142), 43% (61/142), 32.4% (46/142), and 43% (61/142), respectively. The following L1 variations were found in this study: L103F, P104K, P104Y, P104S, D105G, P106S, N108P, F109V, C172S, H228D, and T292A. It was also found that 448S was inserted and 465D was deleted in the L1 amino acid sequences of all the samples. No significant relationship between HPV-16 variants and high-grade lesions was found. Conclusions: The study provides some new data on the genetic diversity of HPV-16, which may help to understand the oncogenic potential of the virus and design the diagnosis reagents and vaccine of HPV in China. Furthermore, in-depth studies are needed to determine the clinical and biological effects of these variants.